Comparison of Post-Operative Outcome of Standard Mass Closure Continuous Technique versus Hughes Repair in Patients Undergoing Exploratory Laparotomy – A Quasi-Experimental Study - Ansari, Sajjad Ahmad; Riaz , Nadia; Awan, Afzal Saeed; Wyne, Adeel; Saleem, Saadan; Kanwal, Saima (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare post-operative outcome of mass closure technique versus Hughes repair in patients undergoing exploratory laparotomy.Study Design: Quasi experimental study.Place and Duration of Study: Department of Surgery, Combined Military Hospital, Multan Pakistan, from Dec 2022 to Jun 2024.Methodology: One hundred and fifty patients of age >20 years undergoing elective or emergency laparotomy were distributed in two groups on basis of repair technique used for laparotomy closure. Patients who underwent Hughes repair were placed in Group-S (study group) and standard mass closure patients were placed in Group-C (Control group). Procedural outcome in term of post-operative incisional hernia at six month was assessed and analyzed in both groups.Results: A Total 150 patients were included in final analysis with mean age of 47.23±9.86 years in Group-S (Hughes repair) and 47.82±9.44 years in Group-C (standard mass closure) (p=0.712). Post-operative complications were also noted and compared in both groups and Hughes repair group had lesser occurrence of post-op complications in comparison to standard mass closure group (p=0.142). At 6th month follow-up, incisional hernia was seen in 9(11.4%) and 17(23.9%) participants of Hughes repair and mass closure respectively (p=0.046). Odds ratio (OR) for the occurrence of incisional hernia at six months follow-up was